2011
DOI: 10.1016/j.jiph.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Listeria monocytogenes and other Listeria species in foods of animal origin in Addis Ababa, Ethiopia

Abstract: Listeriosis is a disease of humans and animals, in which it is one of the important emerging bacterial zoonotic diseases worldwide. Among the different species of the genus Listeria, Listeria monocytogenes (L. monocytogenes) is known to cause listeriosis in humans and animals with low incidence but high case fatality rate. Information on the occurrence and distribution of L. monocytogenes and other Listeria species is very limited both in the veterinary and public health sectors in Ethiopia. The objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
47
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 25 publications
12
47
2
Order By: Relevance
“…However, findings of the present study are comparable with a previous study, which reported prevalence of L. monocytogenes in some foods, such as, meat, cheese, fish, pork, poultry and ice cream, to be 5.1% [17]. Gebretsadik et al [20] also reported a 5.4% prevalence for L. monocytogenes from different food items analyzed, such as Ethiopian cottage cheese, raw beef, raw milk and liquid whole egg; with raw milk being the most contaminated one (13%). In Botswana, a total of 1,324 food samples obtained from supermarkets and street vendors were analyzed for the presence of L. monocytogenes of which 57(4.3%) were found positive.…”
Section: Discussionsupporting
confidence: 90%
“…However, findings of the present study are comparable with a previous study, which reported prevalence of L. monocytogenes in some foods, such as, meat, cheese, fish, pork, poultry and ice cream, to be 5.1% [17]. Gebretsadik et al [20] also reported a 5.4% prevalence for L. monocytogenes from different food items analyzed, such as Ethiopian cottage cheese, raw beef, raw milk and liquid whole egg; with raw milk being the most contaminated one (13%). In Botswana, a total of 1,324 food samples obtained from supermarkets and street vendors were analyzed for the presence of L. monocytogenes of which 57(4.3%) were found positive.…”
Section: Discussionsupporting
confidence: 90%
“…isolated was L. innocua (5.5%). This finding was in agreement with earlier report (Abrahao et al, 2008;Gebretsadik et al, 2011;Rahimi et al, 2012;Jamali et al, 2013). L. monocytogenes was isolated from only raw milk (0.5%) in this study.…”
Section: Discussionsupporting
confidence: 94%
“…L. innocua was known to be the highest prevalent Listeria spp. (Gebretsadik et al, 2011). In the present study, the dominant Listeria spp.…”
Section: Discussionsupporting
confidence: 48%
“…Human infections mainly result from consuming contaminated foods, which may lead to serious and potentially life-threatening listeriosis [31]. Pregnant women, children, elders, people with inadequate immune system [32], alcoholics, drug abusers, patients with corticosteroid therapy and AIDS patients are particularly susceptible to listeriosis [33], which typically presents as septicaemia, meningitis, or meningoencephalitis, intrauterine infection; and sometimes death are reported [31,32].…”
Section: In Humansmentioning
confidence: 99%